2020
DOI: 10.1137/20m1316822
|View full text |Cite
|
Sign up to set email alerts
|

Three-Precision GMRES-Based Iterative Refinement for Least Squares Problems

Abstract: With the recent emergence of mixed precision hardware, there has been a renewed interest in its use for solving numerical linear algebra problems fast and accurately. The solution of least squares (LS) problems min x ∥b − Ax∥ 2 , where A ∈ R m×n , arise in numerous application areas. Overdetermined standard least squares problems can be solved by using mixed precision within the iterative refinement method of Björck, which transforms the least squares problem into an (m + n) × (m + n) "augmented" system. It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Carson et al (2020) show that the three-precision iterative refinement approach of Carson and Higham (2018) can be applied in this case; the theorems developed in Carson and Higham (2018) for the forward error and normwise and componentwise backward error for iterative refinement of linear systems are applicable. The only thing that must change is the analysis of the method for solving the correction equation, since we now work with a QR factorization of A , which can be used in various ways.…”
Section: Dense Linear Algebramentioning
confidence: 99%
See 4 more Smart Citations
“…Carson et al (2020) show that the three-precision iterative refinement approach of Carson and Higham (2018) can be applied in this case; the theorems developed in Carson and Higham (2018) for the forward error and normwise and componentwise backward error for iterative refinement of linear systems are applicable. The only thing that must change is the analysis of the method for solving the correction equation, since we now work with a QR factorization of A , which can be used in various ways.…”
Section: Dense Linear Algebramentioning
confidence: 99%
“…The work in Carson et al (2020) also extends the GMRES-based refinement scheme of Carson and Higham (2017) to the least squares case and shows that one can construct a left preconditioner using the existing QR factors of A such that GMRES provably converges to a backward stable solution of the preconditioned augmented system. Further, it is shown that an existing preconditioner developed for saddle point systems can also work well in the GMRES-based approach in practice, even though the error analysis is not applicable.…”
Section: Dense Linear Algebramentioning
confidence: 99%
See 3 more Smart Citations